Public Participation GIS for sustainable urban mobility planning: methods, applications and challenges - Michał Czepkiewicz; Cezary Brudka; Piotr Jankowski; Tomasz Kaczmarek; Zbigniew Zwoliński; Łukasz Mikuła; Edyta Bąkowska; Marek Młodkowski; Michał Wójcicki (Rozwój Regionalny i Polityka Regionalna)
Sustainable mobility planning is a new approach to planning, and as such it requires new methods of public participation, data collection and data aggregation. In the article we present an overview of Public Participation GIS (PPGIS) methods with potential use in sustainable urban mobility planning. We present the methods using examples from two recent case studies conducted in Polish cities of Poznań and Łodź. Sustainable urban mobility planning is a cyclical process, and each stage has different data and participatory requirements. Consequently, we situate the PPGIS methods in appropriate stages of planning, based on potential benefits they may bring into the planning process. We discuss key issues related to participant recruitment and provide guidelines for planners interested in implementing methods presented in the paper. The article outlines future research directions stressing the need for systematic case study evaluation.